Wybrane zagadnienia wnioskowania temporalnego - Jakubczyc, Janina A.; Mach, Maria A. (Temporal reasoning - selected issues, 2005)
The paper deals with the problems of time representation, temporal reasoning and its applications in the artificial intelligence area. First we present the motivation for reasoning about change, or broadly speaking: temporal reasoning, in the field of AI. We shortly depict and analyse 5 main research areas where temporal issues may be found: databases, expert systems, planning, robotics, and natural language understanding. A significant part of the paper is devoted to theoretical questions, such as the origin of temporal logics and reasoning, Newtonian paradigm, time dependent and time independent models of the world. The last part of the paper presents two main approaches to temporal reasoning: a model approach and an approach based on temporal languages. The first one is discussed using an example of the situation calculus and its application to adaptive databases. The second one is presented with the TAL language as an example. Summing up, the paper is an attempt to order information about temporal representation, reasoning and its practical applications.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 100-122
Keywords: time; change; temporal reasoning; temporal models